Perubahan Struktur Sosial Masyarakat sebagai Akibat dari Konflik Agraria di Sumatera Timur Tahun 1946 - Rizka Hanifah Febriana Rizka Hanifah Febriana (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2023)
This article as a whole discusses a sudden transformation of the social order of society on the island of Sumatra. Then the change in society is influenced by the existence of agrarian conflicts which cannot be separated from the political aspect. The pattern of society that was originally still simple suddenly became more complex due to the existence of a new policy that brought immigrants flocking to East Sumatra to try out the regulations belonging to the Dutch East Indies government in classifying land ownership systems. The purpose of writing this article is based on changes in social attitudes due to agrarian conflicts in East Sumatra. The procedure for developing the discussion is carried out using a qualitative descriptive method based on data sourced from the reading literature and bibliography. The author also tries to present the use of explorative interpretation or meaning. The results of this study as a whole explain the rise of local rulers to a higher position in society and the movement of these communities in maintaining their full power over their land rights. General or joint tenure of land leads to tenure systems of several different types.